Malignant Pancreatic Extra-Gastrointestinal Stromal Tumor Diagnosed by Ultrasound Guided Fine Needle Aspiration Cytology. A Case Report with a Review of the Literature - Rao, Ram Nawal; Vij, Mukul; Singla, Nidhi; Kumar, Ashok (JOP. Journal of the Pancreas, 2011)
Context Pancreatic extra-gastrointestinal stromal tumors are extremely uncommon neoplasm. To the best of our knowledge, only eleven cases have been reported in the literature. All the case reports published mostly involve diagnoses made on surgical pathology. Case report A 40-year-old male patient presented with asthenia, mild abdominal pain, severe anemia and weight loss. Contrast-enhanced computed tomography of the abdomen revealed a heterogeneously enhancing mass (6.5x6.0 cm) in the body and head of the pancreas. Ultrasound-guided fine needle aspiration (US-FNA) was performed on the mass of the pancreas before a pancreaticoduodenectomy. A cytological diagnosis of pancreatic malignant mesenchymal neoplasm was made. The final diagnosis of primary pancreatic extra-gastrointestinal stromal tumor was confirmed by histopathological examination and immunohistochemical findings (CD117 positivity). This case was diagnosed by percutaneous transabdominal ultrasound, rather than endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) which had been used in three previous cases. Conclusion We report a very unusual case of pancreatic extra-gastrointestinal stromal tumor which was diagnosed by US-FNA cytology. Although this is uncommon in the pancreas, extra-gastrointestinal stromal tumors should be considered in the differential diagnosis of solid and cystic pancreatic masses on cytology. Image: A solid mass in the head and body of the pancreas measuring 6.5x6.0 cm with a variegated cut surface.